Review paperThe most common mistakes on dermatoscopy of melanocytic lesions - Kamińska-Winciorek, Grażyna; Placek, Waldemar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Dermatoscopy is a method of in vivo evaluation of the structures within the epidermis and dermis. Currently, it may be the most precise pre-surgical method of diagnosing melanocytic lesions. Diagnostic errors may result in unnecessary removal of benign lesions or what is even worse, they can cause early and very early melanomas to be overlooked. Errors in assessment of dermatoscopy can be divided into those arising from failure to maintain proper test procedures (procedural and technical errors) and knowledge based mistakes related to the lack of sufficient familiarity and experience in dermatoscopy. The article discusses the most common mistakes made by beginner or inexperienced dermatoscopists.